GEOMORFOLOGIA AMBIENTAL - de Melo, Felippe Pessoa (Boletim de Geografia, 2017)
Resenha do livro: GUERRA, Antonio José Teixeira; MARÇAL, Mônica dos Santos. (ORG.). Geomorfologia ambiental. 3ª. ed. Rio de Janeiro: Bertrand Brasil, 2010. 189 p.